A structured argumentation system with backing and undercutting - Cohen, Andrea (2016)
This work introduces Extended Defeasible Logic Programming (E-DeLP), a structured argumentation system enabling the expression of reasons for and against using defeasible rules. E-DeLP extends the formalism of Defeasible Logic Programming (DeLP) by incorporating two new kinds of rules: backing and undercutting rules. In that way, E-DeLP accounts for Toulmin´s notion of backing and Pollock´s notion of undercut, two important contributions within the field of argumentation. Thus, E-DeLP constitutes a novel approach, being the first structured argumentation system in providing a unified setting for modeling Toulmin´s and Pollock´s ideas simultaneously.